Ecosystem services come to town : greening cities by working with nature - Grant, Gary, 1958-; Wiley InterScience (Online service) (Hoboken : Wiley-Blackwell, 2012)
The need to find new approaches to the development of cities is becoming increasingly urgent in this age of continuing population growth, demographic transition, climate change, fossil fuel peak and biodiversity losses. Restoring ecosystem services and promoting biodiversity is essential to sustainable development & ndash; even in the built environment. Ecosystem Services come to Town: greening cities by working with nature demonstrates how to make urban environments greener. It starts by explaining how, by mimicking nature and deliberately creating habitats to provide ecosystem services, citie.
Front Matter -- Introduction -- Origins of Cities -- Modern Cities -- Issues Facing Contemporary Cities -- Working with Nature -- Urban Nature -- Water and Cities -- City-wide Greening -- Greening Neighbourhoods and Buildings -- Conclusion -- Award Winning Projects from IHDC Website -- Useful Resources -- Notes and References -- Index -- Other Books Available from Wiley-Blackwell -- Keep up with Critical Fields.
Includes bibliographical references and index.
Print version record.
Keywords: City planning -- Environmental aspects; Sustainable urban development; ARCHITECTURE -- Urban & Land Use Planning; POLITICAL SCIENCE -- Public Policy -- City Planning & Urban Development; City planning -- Environmental aspects; Sustainable urban development; Electronic books; Electronic books